Thematic Structure in Students’ Writings: Implications on their Ideas Organization and Development - Zefki Okta; Ashadi Ashadi; Sulis Triyono; Dwiyanto Djoko Pranowo (Register Journal, 2023)
Thematic structure is an important concept in organizing ideas in academic writing. Although numerous studies have focused on investigating how it is realized in students' writing, only a few focus on investigating thematic structure in students' text across different proficiency levels. This article is based on a study analyzing idea organization and development in 24 high and low-scoring essays through Systemic Functional Linguistics (SFL). It was a qualitative content analysis with complementary quantitative data. The results show significant differences in how ideas are organized and developed in high and low-scoring essays. Even though all types of Themes (topical, interpersonal, textual Theme) were observed in both groups, the high-scoring essays elaborated more themes than the low ones indicating that the high-scoring essays comprised more clauses. As for Thematic Progression, all the patterns were present in the essays. The Linear Theme pattern was primarily applied in high-scoring essays, while the Constant Theme pattern was applied frequently in the low-scoring ones. The Split Rheme pattern was less observed in all the students' essays. These findings indicate that the high achievers provided more expounded ideas through linear theme patterns, whereas their counterparts tended to focus on a subject reflected through Theme reiteration. Thus, this implies that proficiency characterized writers in organizing and developing ideas in writing as reflected through thematic Choice and Progression.